Hydrogen Sulfide Ameliorates Lung Ischemia-Reperfusion Injury Through SIRT1 Signaling Pathway in Type 2 Diabetic Rats - Jiang, Tao; Yang, Weiwei; Zhang, Hongli; Song, Zhiqiang; Liu, Tianhua; Lv, Xiangqi (Frontiers in Physiology, 2020)
Lung ischemia-reperfusion (IR) injury remains a significant factor for the early mortality of lung transplantations. Diabetes mellitus (DM) is an independent risk factor for 5-year mortality following lung transplantation. Our previous study showed that DM aggravated lung IR injury and oxidative stress played a key role in this process. Previously, we demonstrated that H2S protected against diabetic lung IR injury by suppressing oxidative damage. This study aimed to examine the mechanism of H2S on diabetic lung ischemia-reperfusion injury. High-fat diet-fed streptozotocin-induced type 2 diabetic rats were exposed to GYY4137, a slow-releasing H2S donor with or without administration of EX527 (a SIRT1 inhibitor), and then subjected to a surgical model of ischemia-reperfusion injury of the lung. Lung function, oxidative stress, cell apoptosis, inflammation were assessed. We found that impaired lung SIRT1 signaling under type 2 diabetic conditions was further attenuated by ischemia-reperfusion injury. GYY4137 treatment markedly activated SIRT1 signaling and ameliorated lung IR injury in type 2 DM animals by improving lung functional recovery, diminishing oxidative damage, reducing inflammation and suppressing cell apoptosis. However, these effects were largely compromised by EX527. Additionally, treatment with GYY4137 significantly activated Nrf-2/HO-1 antioxidant signaling pathway and increased eNOS phosphorylation. However, these effects were largely abolished by EX527. Together, our results indicate that GYY4137 treatment effectively attenuated lung IR injury under type 2 diabetic conditions via activation of lung SIRT1 signaling. SIRT1 activation upregulated Nrf-2/HO-1 and activated eNOS mediated antioxidant signaling pathway, thus reducing cell apoptosis and inflammation, and eventually preserving lung function.